On elastic impact and dynamic hardness (Archives of Mechanics - Test, 2000)
Colinear impact and dynamic hardness is analyzed at spherical contact and moderate strains. A consistent three-dimensional contact theory based on viscoplastic material behaviour is laid down involving elements of self-similarity, stationary boundary conditions and cumulative superposition. Universal relations between impact velocity and the resulting contact region, impression depth and duration of impact are derived. Deformed surface shapes are shown to be self-similar for power law material behaviour and their relation to piling-up and sinking-in is explained in detail. The coefficient of restitution at rebound is estimated to first order. The concept of dynamic hardness is not unequivocally defined in general and various definitions in literature are discussed in relation to true material rate sensitivity. Theoretical and numerical predictions of the present model are compared with pertinent experimental findings for different metals. Particular features such as lip formation, plastic zone size and maximum penetration depth are elucidated.